Kingdom of Netherlands : Netherlands; Financial System Stability Assessment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The Netherlands has been heavily affected by the global financial crisis. The 'Twin Peaks' supervision model, with Netherlands Central Bank - De Nederlandsche Bank (DNB) as the prudential supervisor, and the Authority for Financial Markets (AFM) responsible for conduct-of-business supervision, was severely tested, although the case for the model remains strong. The crisis has shown that these institutions bring sizable risks, which requires careful and comprehensive monitoring and supervision. The findings of the Financial Stability Assessment Program (FSAP) are summarized. Top-down stress tests were conducted. Supervisory colleges are an important innovation to reinforce home-host coordination for supervisors of large complex financial institutions (LCFIs).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet